2019
DOI: 10.1111/aogs.13561
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labor at full‐term in pregnant women with uncomplicated singleton pregnancy: A systematic review and meta‐analysis of randomized trials

Abstract: Introduction The lowest incidence of perinatal morbidity and mortality occurs around 39‐40 weeks. Therefore, some have advocated induction of uncomplicated singleton gestations once they reach full‐term. The aim of the study was to evaluate the risk of cesarean delivery, and any maternal and perinatal effects of a policy of induction of labor in women with full‐term uncomplicated singleton gestations. Material and methods We performed an electronic search from inception of each database to August 2018. All res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 40 publications
5
35
0
4
Order By: Relevance
“…The latest contribution is that of the Maternal–Fetal Medicine Units Network which, in August 2018 31 , published the results of a multicenter trial that included 6,106 low-risk women randomized to receive IOL at 39 0 –39 4 weeks or expectant management. The primary outcome of the study was a composite of perinatal death or severe neonatal complications and the conclusions were that elective induction does not reduce the composite adverse perinatal outcome but nevertheless results in a significantly lower frequency of cesarean delivery (18.6% versus 22.2%; relative risk 0.84; 95% confidence interval [CI] 0.76 to 0.93) However, a most recent systematic review and meta-analysis of 7 randomized controlled trials with 7598, has shown no effect on the cesarean delivery rates 32 . The rationale for elective inductions would be to manage pregnancies between 39 0 and ≤41 0 weeks, as before and after these gestational ages perinatal outcomes are worse than at term 9, 33 .…”
Section: Precursors For Inductionmentioning
confidence: 99%
“…The latest contribution is that of the Maternal–Fetal Medicine Units Network which, in August 2018 31 , published the results of a multicenter trial that included 6,106 low-risk women randomized to receive IOL at 39 0 –39 4 weeks or expectant management. The primary outcome of the study was a composite of perinatal death or severe neonatal complications and the conclusions were that elective induction does not reduce the composite adverse perinatal outcome but nevertheless results in a significantly lower frequency of cesarean delivery (18.6% versus 22.2%; relative risk 0.84; 95% confidence interval [CI] 0.76 to 0.93) However, a most recent systematic review and meta-analysis of 7 randomized controlled trials with 7598, has shown no effect on the cesarean delivery rates 32 . The rationale for elective inductions would be to manage pregnancies between 39 0 and ≤41 0 weeks, as before and after these gestational ages perinatal outcomes are worse than at term 9, 33 .…”
Section: Precursors For Inductionmentioning
confidence: 99%
“…A systematic review by Saccone et al published in this issue of AOGS further supports the view that elective IOL at term is not associated with increased risk of CS . Not surprisingly, there was also less risk of meconium staining of the amniotic fluid in the IOL group.…”
mentioning
confidence: 69%
“…While their premise could not be confirmed, they demonstrated that elective induction reduced the rates of CD (18.6% vs. 22.2%; p < 0.001) and hypertensive disorders (9.1% vs 14.1%; p < 0.001). These results were subsequently supported by three meta-analyses [7][8][9] showing that the conclusions of the ARRIVE Trial do not appear to be limited to a research setting.…”
Section: The Arrive Trialmentioning
confidence: 82%